The Use of Digital Book Media to Improve Writing Skills of Explanatory Text - Muhammad Akhir (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to examine the usage of digital book media in the development of explanatory texts for students in the sixth grade of primary school. The experimental design employed in this study was a one-group pretest-posttest design. Test in command questions is used to collect data, which is then used to produce explanatory texts utilizing digital book media. The paired sample t-test on the SPSS Version 22 system is used for this normality test, and the results are presented in the following table. The results of the study revealed that the pre-test mean was 66.11. In contrast, the post-test mean was 82.78, indicating that the post-test score was more dominant than the pre-test based on descriptive statistical analysis approaches. H0 is rejected, while H1 is approved, indicating an effect of utilizing digital book media on writing skills in the sixth grade of elementary school, according to the findings of the study.